Bioaccumulation and Bound-Residue Formation of a Branched 4-Nonylphenol Isomer in the Geophagous Earthworm Metaphire guillelmi in a Rice Paddy Soil - Shan, Jun; Wang, Ting; Li, Chengliang; Klumpp, Erwin; Ji, Rong (Environmental science & technology, 2010)
Nonylphenols (NPs) are the breakdown products of the nonionic surfactants nonylphenol ethoxylates and are toxic pollutants. Here we studied the bioaccumulation, elimination, and biotransformation of NP (12.3 mg kg−1 soil dry weight) in a typical Chinese geophagous earthworm, Metaphire guillelmi, in a rice paddy soil, using 4-[1-ethyl-1,3-dimethylpentyl]phenol (4-NP111), the main constitute of technical NP, radiolabeled with 14C. Earthworms rapidly bioaccumulated 14C-4-NP111 following a two-compartment first-order kinetics model. At steady state (after 20 days exposure), the normalized biota-soil accumulation factor amounted to 120, and 77% of the accumulated radioactivity were present as nonextractable bound residues. The total radioactivity was eliminated from the earthworm following an availability-adjusted decay model and controlled by the elimination rate of the bound residues (half-life = 22.6 days). The extractable residues consisted mainly of one less-polar metabolite (37%) and polar compounds (50%), including glucuronide conjugates of 4-NP111 and the metabolite; and free 4-NP111 accounted for only 9% of the total extractable residues. This study provides the first results of the toxicokinetics and biotransformation of 4-NP in a terrestrial organism, and underlines the significant underestimation of the bioaccumulation and risk assessment based only on free NP in earthworms.